Pengambilan Pati Dari Batang Sawit - Saparullah, Zulkarnaen; Zulfansyah, Zulfansyah; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The replanting of oil palm produced 70.2 tons per hectare of solid palm oil waste. The utilization of palm oil waste has been limited. One alternative to deal with this problem is by extracting starch contained in the oil palm trunk. The purpose of this study is to extract starch and determine the effect of process conditions on starch quality. starch extraction was carried out under atmospheric conditions with 125 gram weight of palm stem powder, sodium metabisulfite concentration (0.25%, 0.5% and 0.75%), extraction time (12 hours, 24 hours and 36 hours) and liquid solid ratio 15/1 ( b / b). The result should highest starch content was obtained at a solvent concentration of 0.5% with an extraction time of 24 hours and a liquid solids ratio of 15/1. Keywords : oil palm trunk, extraction, starch,